Plasma Concentration of 12-Hydroxyeicosatetraenoic Acid, Single Nucleotide Polymorphisms of 12-Lipooxygenase Gene and Vaso-Occlusion in Sickle Cell Disease - Duru, Augustine Nwakuche; Ocheni, Sunday; Ibegbulam, Obike; Okpala, Iheanyi (Frontiers in Genome Editing, 2021)
Abstract Background and novel aspect of this work In the light of previous findings that inflammation predisposes to intercellular adhesion and microvascular occlusion in sickle cell disease (SCD), this study investigated the relationship between the number of vaso-occlusive events in SCD, plasma levels of the pro-inflammatory molecules 12-Hydroxyeicosatetraenoic acid (12-HETE), TNF-α and IL-1β; and single nucleotide polymorphisms (SNPs) in the gene 12-Lipooxygenase (ALOX-12), which encodes the enzyme 12-Lipoxygenase that catalyzes the biosynthesis of 12-HETE. Objective To evaluate the relationship between vaso-occlusion in SCD and plasma concentrations of 12-HETE, TNF-α, and IL-1β; and single nucleotide polymorphisms (SNPs) in ALOX-12 gene. Participants and Methods In 50 HbSS patients, the numbers of vaso-occlusive crisis requiring hospital treatment in the previous one year and the vaso-occlusive complications of SCD developed to datte (e.g stroke) were added to obtain the vaso-occlusive events (VOE) score. In the HbSS patients and 30 healthy sibling control persons, plasma concentrations of 12-HETE, TNF-α and IL-1β were measured by ELISA, the ALOX12 SNPs rs2073438 and rs1126667 detected by DNA sequencing, and the accrued data statistically analysed. Results Compared to SCD patients with VOE score 0-1, those with scores >3 had higher plasma levels of 12-HETE (p <0.0001) and TNF-α (p = 0.19), but not IL-1β (p = 0.27). VOE score showed strong direct correlation with plasma level of 12-HETE (r = 0.65, p < 0.0001), but not with TNF-α nor IL-1β. Neither VOE score nor plasma concentration of 12-HETE showed any relationship with the ALOX12 SNPs rs2073438 and rs1126667. Conclusion The strong direct correlation of VOE score with plasma concentration of 12-HETE suggests that the clinical relevance of this pro-inflammatory molecule in SCD-associated vaso-occlusion needs to be evaluated in further studies.